Psychometric properties of the malay version of the personal wellbeing index: a preliminary study among caregivers of children with autism spectrum disorder - Shobnaa Tinagaran,; Hanif Farhan Mohd Rasdi,; Dzalani Harun,; Kamaruddin Hassan,; Shahirah Md Rasid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Caregivers of children with Autism Spectrum Disorder (ASD) can have a compromised quality of life due to caregiving burden and parenting stress. The Personal Wellbeing Index (PWI) is one of the instruments that measure the subjective wellbeing dimension. This study intended to explore this instrument’s construct validity and reliability and compare the subjective wellbeing among caregivers based on sociodemographic characteristics. A cross-sectional study was conducted on 53 caregivers of children with ASD recruited from occupational therapy clinics at Hospital Canselor Tuanku Muhriz (HCTM) and the Faculty of Health Sciences, UKM. The PWI has one global life satisfaction construct (1 item) and subjective wellbeing (8 items). The rating scale is anchored from 0 (no satisfaction at all) to 10 (completely satisfied). The statistical analysis indicated that the Malay version of PWI has acceptable unidimensionality (outer loadings >0.5 for all items), convergence validity (Average Variance Extracted (AVE)=0.5781), constructs validity (r=0.812, p<0.001), and construct reliability (ρA=0.8864, ρc=0.9046, α=0.8761). Marital status is significant in achieving life and personal relationships while health issues are significant only in personal health. The Malay version has good construct validity and reliability and can measure the subjective wellbeing of the caregivers of children with autism in Malaysia. The psychometric properties of the PWI Malay version can be further established with a larger sample size. In the future, a national norm of Malaysians’ wellbeing could be developed to interpret their wellbeing level.